1987
DOI: 10.1111/j.1365-246x.1987.tb01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Large variation of Curie depth and lithospheric thickness beneath the Indian subcontinent and a case for magnetothermometry

Abstract: A first order estimate of Curie depth and lithospheric thickness variation beneath the Indian region has been obtained using the available geothermic data. The Curie depth is found to vary from 18 to 68 km and the lithospheric thickness from 38 to 186 km. These estimates conform well with the MAGSAT and seismological findings. Both the parameters exhibit covariancy and suggest the possibility of approximating heat flow values and lithospheric thickness in geothermally uncharted areas using Curie point geotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 36 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…8) passing over the conductor have been investigated. In the absence of crustal radioactivity information near the Ujjain-Guna region, lithospheric thickness and depth to the Curie-point isotherm have been estimated, based on the relationship given by NEGI et al (1987). The calculation suggests that this region has a relatively thick lithosphere of approximately 140 km and depth to the Curie-point isotherm at about 50 km.…”
Section: Resultsmentioning
confidence: 99%
“…8) passing over the conductor have been investigated. In the absence of crustal radioactivity information near the Ujjain-Guna region, lithospheric thickness and depth to the Curie-point isotherm have been estimated, based on the relationship given by NEGI et al (1987). The calculation suggests that this region has a relatively thick lithosphere of approximately 140 km and depth to the Curie-point isotherm at about 50 km.…”
Section: Resultsmentioning
confidence: 99%
“…Further, observed surface heat flow has often been correlated with the thickness of the lithosphere Crough and Thompson, 1976;Negi et. al, 1987).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Based on mantle derived paleo-geotherms on these xenoliths, a minimum heat flow between 60 and 70 mW m −2 has been projected for this region by Mukherjee and Biswas (1988), following the method of calculation from Pollack and Chapman (1977). Similarly, empirical relationships given by Negi et al (1987) and Chapman and Pollack (1977) would also result in a surface heat flow of about 60 to 75 mW m −2 against a lithospheric thickness of 70 km, which is quite accurately known (Fig. 4).…”
Section: Heat Flow Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the Curie depth is non-uniform and may range from 6 to 40 km (SHUEY et al, 1977;LACHENBRUCH and SASS, 1977;MAYHEW, 1982). NEGI et al (1987), based upon the data from MAYHEW (1982) and Indian data, suggested that the heat flow decreases exponentially with an increase in Curie depth. However, the relationship between heat flow (Q) and Curie depth (H) can be better represented by the function with a correlation factor of 0.99 (Fig.…”
Section: Surface Heat Flow Estimatesmentioning
confidence: 99%